FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN MINUM OBAT PADA PASIEN DIABETES MELITUS TIPE 2 YANG MENJALANI PERAWATAN DI RSUD YULIDDIN AWAY TAPAKTUAN TAHUN 2025 - Nada Amirah; Sri Sudewi Pratiwi Sitio; Ira Risnawati; Bahtera Bindavid Purba (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2026)
Type 2 Diabetes Mellitus is a chronic disease characterized by low medication adherence, which can lead to severe complications. This study aimed to analyze the factors influencing medication adherence among Type 2 DM patients at Yuliddin Away Regional General Hospital, Tapaktuan. This quantitative analytic research used a cross-sectional design, with 92 respondents selected using purposive sampling based on specific inclusion criteria. The results showed that the majority of respondents were aged ≥50 years (54.3%), female (58.7%), and had low medication adherence (60.9%). Statistical analysis revealed no significant relationship between knowledge (p=0.428) and education (p=0.096) with adherence. However, significant relationships were found between attitude (p=0.0001), family support (p=0.0001), and health worker support (p=0.0001) and medication adherence. These findings highlight the importance of psychosocial factors and the involvement of family and healthcare providers in improving patient adherence. It is recommended that the hospital enhance counseling and patient education programs and actively involve families in the treatment process. Patients are encouraged to adopt a more positive attitude, maintain communication with healthcare providers, and seek family support to ensure consistent medication adherence.